2023
DOI: 10.1097/nne.0000000000001357
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Judgment Development and Assessment in Clinical Nursing Education

Abstract: Background: There is a gap in evidence for effective clinical teaching strategies to promote nursing students' development of clinical judgment (CJ). Purpose: This study examined the effect of active learning strategies (ALSs) during clinical postconference sessions on the CJ of undergraduate nursing students. Methods: This quasi-experimental study of ALSs or standard postconferences used the Lasater Clinical Judgment Rubric (LCJR) to rate CJ at 3 time points. All faculty members and students were trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Reflection on performance is a valid method for fostering deeper learning and is important for NGNs as they transition to practice. 2,6 The impetus for this innovative approach was the development of a new course within an existing nursing curriculum, which is described in an article by the authors. 7 SBE was created using the International Nursing Association for Clinical Simulation and Learning (INACSL) standards.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reflection on performance is a valid method for fostering deeper learning and is important for NGNs as they transition to practice. 2,6 The impetus for this innovative approach was the development of a new course within an existing nursing curriculum, which is described in an article by the authors. 7 SBE was created using the International Nursing Association for Clinical Simulation and Learning (INACSL) standards.…”
Section: Introductionmentioning
confidence: 99%
“…This alignment is the key to deeper learning and the basis for assessing performance of clinical judgment, decision-making, and competency. 5,6 Preparation for practice often rests in clinical learning and practicum experiences. Because of the nature of clinical placements in nursing programs, these experiences vary among nursing students, depending on the patient populations and clinical environments to which they are assigned.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Research has demonstrated that clinical debriefing is an important education tool to help students develop clinical judg-ment. [5,6] There is a dearth of evidence concerning clinical debriefing for community/population/public health nursing (CPPH) clinical experiences at the baccalaureate level. Additionally, no evidence was identified describing how CPPH nurse educators help students integrate theory and CPPH clinical experiences to facilitate clinical judgment.…”
Section: Introductionmentioning
confidence: 99%